Fuzzy control of the dual-stage feeding system consisting of a piezoelectric actuator and a linear motor for electrical discharge machining. (April 2020) - Bani Melhem, Muyad K; Simic, Milan; Lai, Chow Yin; Feng, Yong; Ding, Songlin
Gap width is an important factor that affects material removal rate, surface finish, and machining stability in electrical discharge machining processes. This research is to develop a novel control method for a new hybrid positioning system which consists of a linear motor and a piezoelectric actuator for high-efficiency electrical discharge machining processes. In the new system, the linear motor provides the macro feeding while the piezoelectric actuator feeds the workpiece in micro scale at high frequency. To reduce the delay caused by separate movements of the linear motor and piezoelectric actuator, a new control algorithm was developed to synchronize the movements of the motor and piezoelectric actuator. A fuzzy control system was used to control the feeding process. Piezoelectric actuator position and its speed were selected as the fuzzy inputs, while the fuzzy output was the linear motor speed. Cutting experiments were conducted, and results show that the fuzzy system is more powerful than the conventional algorithm and the new algorithm with constant motor speed. An increase in material removal rate of 1.6 times was achieved using the proposed fuzzy control algorithm.